The Political Economy of Financial Systems: Evidence from Suffrage Reforms in the Last Two Centuries - Hans Degryse; Thomas Lambert; Armin Schwienbacher (Center for Economic Studies and ifo Institute (CESifo), 2013)
Initially, voting rights were limited to wealthy elites providing political support for stock markets. The franchise expansion induces the median voter to provide political support for banking development as this new electorate has lower financial holdings and benefits less from the uncertainty and financial returns from stock markets. Our panel data evidence covering 1830-1999 shows that tighter restrictions on the voting franchise induce a greater stock market development, whereas a broader voting franchise is more conducive towards the banking sector, consistent with Perotti and von Thadden (2006). Our results are robust to controlling for other political determinants and endogeneity.
Keywords: D72; G10; O16; P16; 330; banking sector; financial development; financial structure; political economy; stock markets; voting franchise